Integrated Reservoir Study to Optimize Gas Production of Water Drive Gas Reservoir Case Study: Lower Menggala Gas Field - Panca Suci Widiantoro; Astra Agus Pramana; Putu Suarsana; Anis N Utami (Universitas Lampung, 2018)
Production optimization in mature field water drive gas reservoir is not easy especially when water already breakthrough in producing wells. An integrated reservoir study is needed to get reliable strategy to optimize production of water drive gas reservoir. This research presents the integrated reservoir study of Lower Menggala (LM) Gas Field which is located Central Sumatera Basin, Riau Province. LM had been produced since 1997, current RF are 55%, which is quite high for water drive gas reservoir. The current gas rate production is about 1.97 MMscfd with high water production around 4250 BWPD, consequently some of wells suffered liquid loading problem This research comprises of well performance analysis, estimate OGIP, aquifer strength of the reservoir by using conventional material balance method and modern production analysis method then conduct dynamic reservoir simulation to identify the best strategy to optimize gas production. Economic analysis also be performed to guide in making decision which scenario will be selected. DST analysis on DC-01 well defined reservoir parameter, boundary and deliverability which are P*= 2520 psia, k= 229 mD, Total skin= 8, detected sealing fault with distance 175 m, and AOF 45 MMscfd. Conventional material balance method gave OGIP 22.7 BScf, aquifer strength 34 B/D/Psi, whereas modern production analysis estimated OGIP 22.35 BScf, aquifer strength 34 B/D/psi. Those two method shows good consistency with OGIP volumetric calculation with discrepancy OGIP value +/- 1%. Six (6) scenario of production optimization has been analyzed, the result shows that work over in two wells and drilling of 1 infill well (case 6) achieve gas recovery factor up to 75.2%, minimal water production and attractive economic result